2019
DOI: 10.2196/11674
|View full text |Cite
|
Sign up to set email alerts
|

Using an Electronic Tablet to Assess Patients’ Home Environment by Videoconferencing Prior to Hospital Discharge: Protocol for a Mixed-Methods Feasibility and Comparative Study

Abstract: Background Occupational therapists working in hospitals are usually involved in discharge planning to assess patients’ safety and autonomy upon returning home. However, their assessment is usually done at the hospital due to organizational and financial constraints. The lack of visual data about the patients’ home may thus reduce the appropriateness and applicability of the support recommended upon discharge. Although various technological tools such as mobile devices (mobile health) are promising… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In addition, previous studies on pre-discharge visits using information and communication technology tools have reported that mobile videoconferencing by multiple professions has benefits, including more appropriate recommendations by rehabilitation professionals, 12,13 which were also reported in this study as facilitating the exchange of opinions during multidisciplinary conferences and decision-making by multiple professionals. On the other hand, previous studies have pointed out the time limitation of mobile conferencing due to the simultaneous gathering of multiple professions as a disadvantage, but this application has no time limitation and overcomes this limitation.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In addition, previous studies on pre-discharge visits using information and communication technology tools have reported that mobile videoconferencing by multiple professions has benefits, including more appropriate recommendations by rehabilitation professionals, 12,13 which were also reported in this study as facilitating the exchange of opinions during multidisciplinary conferences and decision-making by multiple professionals. On the other hand, previous studies have pointed out the time limitation of mobile conferencing due to the simultaneous gathering of multiple professions as a disadvantage, but this application has no time limitation and overcomes this limitation.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, previous studies have pointed out the time limitation of mobile conferencing due to the simultaneous gathering of multiple professions as a disadvantage, but this application has no time limitation and overcomes this limitation. 12,13 The findings of the current study have several novelties. A novelty of the results of this study is that the use of a video-sharing application can approach the psychological distance between multidisciplinary professionals and promote interprofessional communication and collaboration among multiple professions.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The methods used for this study are detailed in a published protocol [ 17 ]. We conducted a concurrent mixed methods feasibility study to compare 2 home assessment methods ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…3 Given the evidencebased benefits of home assessments and their importance within a rehabilitation hospital setting, it is important to identify time-efficient pre-discharge home assessment delivery methods for this population. Advancements in technology have identified multiple alternative home assessment delivery models, including video-conferencing on electronic tablets, 12 patient-led measurements and remote protocols for carer measurements, 13,14 use of digital photography, 3 and telehealth home assessments. 15 The introduction of digital technology to home assessments for rehabilitation inpatients has the potential to streamline processes and improve time efficiencies where they have not been trialed before compared with usual care.…”
Section: Introductionmentioning
confidence: 99%